1057 Outcome Reporting Following Rectopexy Requires Standardisation for Reproducibility and Transparent Outcome Analysis. (12th October 2021) - Wa Katolo, H; Fleming, C; Wilkinson, G; Brannigan, A
Abstract: Aim: Rectopexy is a surgical procedure commonly used to correct rectal prolapse. Several studies have investigated different approaches (abdominal, perineal) and techniques (open, laparoscopic, robotic) in this field however reporting outcomes vary significantly among studies impeding comparison of techniques. We aimed to comprehensively analyse primary outcome reporting methods following rectopexy in published literature. Method: A systematic search was performed in keeping with PRISMA guidelines and search protocol registered with PROSPERO. Published databases were searched using the following terms: "rectopexy", "abdominal rectopexy" and "rectopexy outcomes". Randomised controlled trials, comparative and non-comparative prospective and retrospective studies published between 1992 and 2019 were included for analysis. Review articles, letters, editorials, abstracts, and non-English language studies were excluded. A narrative description of outcomes was reported. Results: A total of 1089 articles were screened, and 32 articles were identified as suitable for inclusion, reporting on 1780 patients who underwent rectopexy surgery. Over 30 unique methods of reporting outcomes were recorded, with the most common being the rate of recurrence (n = 15), Cleveland Clinic Faecal Incontinence score (CCIS) (n = 11), and customised symptom questionnaires (n = 10). Many studies recognised the impact of symptoms of rectal prolapse on patients' quality of life (QoL) however, few utilised standardised quality of life scores to evaluate the outcome of the procedures. Conclusions: As surgical technique evolves in rectopexy, incorporating minimally invasive surgery and robotic surgery, it is important that outcome reporting is standardised to facilitate transparent comparison. Improving patient QoL is the mainstay of surgical intervention and it is important that QoL outcome measures are incorporated.